P080 Burden of Disease and Cost of Illness of Inflammatory Bowel Diseases in Portugal. (27th May 2021) - Magro, F; Portela, F; Lago, P; Chagas, C; Moreira, F; Pereira, F; Rodrigues, B; Pedrosa, H; Correia, L
Abstract: Background: Estimate the burden of the disease (BoD) of IBD in Portugal and quantify society's cost of illness (CoI) associated, including direct and indirect costs. Raise awareness to IBD in Portugal and thus bringing empowerment to the patient community. Methods: Burden of disease was assessed considering the impact in terms of DALY, estimated considering a prevalence-based model. Costs were estimated considering the societal perspective, using a prevalence-based model. Direct costs comprise hospitalizations, surgeries, medical appointments, emergency visits, pharmacological treatment, exams and transportation. Indirect costs were calculated from patient and caretaker absence, presenteeism, early retirement and premature death. An expert panel composed by 5 Portuguese gastroenterologists and a patient reported study were conducted to support the cost analysis and fill in information gaps. The expert panel followed a two-round modified Delphi methodology. The patient reported study was conducted with 370 Portuguese IBD patients by the Portuguese Association of Inflammatory Bowel Disease (APDI). Results: Considering a prevalence of 24, 070 patients, 6, 067 DALYs were estimated to be lost in Portugal due to IBD. This result reflects a total of 507 YLLs (8%) and a total of 5, 560 YLDs (92%) The total annual cost associated with IBD patients in Portugal was estimated to be €146, 293, 082, with an average annual cost of €6, 075 per patient. This value is divided into €86, 834, 011 direct costs (59%) and €59, 459, 070 (41%) indirect costs. Indirect costs account for 41% of IBD's total cost. Interestingly, costs of patient work absences showed very similar values to those associated with presenteeism. This demonstrates that IBD does not manifest its impact only in isolated timepoints, but rather that it is present in the everyday lives of patients. Conclusion: It is essential to discuss the relationship between the burden of disease and its cost, especially when discussing a clinical condition with an increasing incidence rate in an ageing population as it is in Portugal. Due to the need to generate further data and evidence regarding IBD, this study provides the first comprehensive insight at a national level considering all the dimensions of disease burden. The results presented will raise social-economic awareness of IBD, allow for the definition of disease management strategies and support prioritization on resource allocation, especially considering the availability of new treatment approaches. Moreover, this study will set the basis for the thorough assessment of the real burden of IBD in the Portuguese healthcare system and society overall.